THE DOWRY: BETWEEN RELIGIOUS DOCTRINE AND LOCAL CULTURE - Nurmalia Tara; Muhammad Amar Adly (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2026)
Mahr is one of the essential elements in Islamic marriage that has a strong normative foundation in the Qur'an and the Prophetic Sunnah. However, its implementation across the Muslim world including Indonesia shows significant variation, shaped by local traditions, social structures, and interpretations across the various schools of Islamic jurisprudence. This paper comprehensively examines the provisions of mahr according to the four major legal schools (madhabs) Hanafi, Maliki, Shafi'i, and Hanbali alongside contemporary scholarly perspectives, analyzes the shifting value of mahr within the cultural context of the Nusantara archipelago, including the customary traditions of the Bugis, Minangkabau, Javanese, Batak, and Acehnese peoples, and investigates how the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) and the jurisprudence of the Religious Courts accommodate the tension between normative texts and local traditions. The methodology employed is library research (studi kepustakaan) with comparative, historical, and normative approaches. The findings reveal that despite variations in determining the amount, form, and social function of mahr, all four schools are unanimous regarding its obligatory nature and its function as an expression of respect toward the woman. Contemporary Islamic jurisprudence offers a maqasid al-shari'ah perspective that reinforces the relevance of mahr as an instrument of gender justice. Local Indonesian cultures, in many respects, actually strengthen the substantive principles of Islamic law concerning mahr, although in certain aspects they require adjustment and purification through contextual ijtihad.Keyword: Mahr, Schools of Islamic Jurisprudence, Contemporary Fiqh, Maqasid al-Shari'ah, Local Culture